2023
DOI: 10.15639/teflinjournal.v34i1/136-156
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Gamified Vocabulary Learning in Asynchronous Mode

Abstract: Gamified online quizzes have gained popularity for their potential in enhancing student learning motivations, creating engaging lessons, and improving learning outcomes. Yet, its application and effectiveness in support of student vocabulary learning have only been explored in synchronous learning setting. This study, hence, extended the exploration by examining the implementation of gamified vocabulary learning in an asynchronous mode and analyzing the impacts on students’ learning outcomes in class. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This is still recognized by most educators today, as evidenced by the numerous papers on exams, tests, and quizzes reported that have been reported specifically since the year 2020. Among these, papers on quiz creation methods include: 1) tools for creating online quizzes (for example, Shaik et al, 2020), 2) the effects of gamification for enjoyable learning (for example, Waluyo & Tran, 2023;Daulay & Adelita, 2023;Segaran & Hashim, 2022), and 3) cheating prevention measures for fairness (for example, Newton & Essex, 2023;Holden et al, 2021;Zulkifli & Khalid, 2023).…”
Section: Personal Skills Needed For Successful Implementationmentioning
confidence: 99%
“…This is still recognized by most educators today, as evidenced by the numerous papers on exams, tests, and quizzes reported that have been reported specifically since the year 2020. Among these, papers on quiz creation methods include: 1) tools for creating online quizzes (for example, Shaik et al, 2020), 2) the effects of gamification for enjoyable learning (for example, Waluyo & Tran, 2023;Daulay & Adelita, 2023;Segaran & Hashim, 2022), and 3) cheating prevention measures for fairness (for example, Newton & Essex, 2023;Holden et al, 2021;Zulkifli & Khalid, 2023).…”
Section: Personal Skills Needed For Successful Implementationmentioning
confidence: 99%